Diversidade genética e possíveis rotas de dispersão de Thaumastocoris peregrinus (Hemiptera: thaumastocoridae) - Machado, Dayanna do Nascimento (2020)
The bronze bug, Thaumastocoris peregrinus, native from Australia, has become an invasive pest almost worldwide for the past 16 years and is causing significant damage to Eucalyptus and Corymbia trees. The rapid spread of T. peregrinus raised some questions about possible routes used by this insect to invade continents. In this sense, this study aimed to investigate the genetic diversity of 11 populations of T. peregrinus from the new and old world countries, and to infer possible routes of T. peregrinus dispersal using a fragment of the Cytochrome Oxidase subunit I (COI) gene. Specimens of T. peregrinus were collected between 2016-2019 from Argentina, Brazil, Chile, Spain, the United States, Israel, Italy, Mexico, Paraguay, Portugal and Uruguay, were stored in tubes containing 92% or absolute alcohol, and were sent to the Agricultural Biotechnology Laboratory of the Federal University of Santa Maria (Santa Maria, Rio Grande do Sul, Brazil) for molecular characterization. Mitochondrial DNA (mtDNA) data from these specimens were combined with sequences deposited at Genbank and non-deposited, to perform a haplotype network. Possible T. peregrinus invasion routes have been suggested based on: (1) space-time invasion events; (2) literature reports of invasion routes in each country; (3) movement of people, goods, timber by road and sea routes between countries; and (4) mtDNA sequences from T. peregrinus populations. A total of 126 T. peregrinus mtDNA sequences from 29 sites were obtained from 11 countries. Combined data gererated a total of 423 sequences. Haplotype A was the most dispersed worldwide and nine invasion routes were suggested. This is the first molecular characterization performed for T. peregrinus populations in Chile, Paraguay, Mexico, United States, Portugal, Spain and Israel. T. peregrinus haplotype A is dominant in the populations sampled in its invasive range. For Italy we inform for the first time the presence of haplotype A and the increased of genetic diversity of T. peregrinus in this country. The possible invasion scenarios suggested for this insect pest can aid to clarify some paths used in its dispersal.